PRINSIP-PRINSIP PENDIDIKAN ISLAM - Widya Ayu Ningsih; Intan Ayu Permata (Jurnal At-Tabayyun, 2022)
As we know that the main source of islamic education is the holy book al-qur'an and sunnah rasulullah saw. As well as the opinions of friends and muslim scholars or scientists in addition. Islamic education as a scientific discipline must open one's eyes that the current state of education is far from what we expect. This journal was made to find out what is the meaning of principles and islamic education. The basic principles of islamic education mean a basic view of something that is the main source so that it becomes the concept, value and foundation of islamic education. The basic principles of islamic education include Bottom of Form The principle of Islamic education is also upheld on the same basis and stems from the philosophical view of Islam towards the universe, humans, society, science and morals. The Islamic view of these problems gave birth to various principles in Islamic education.